2017
DOI: 10.28989/angkasa.v7i2.160
|View full text |Cite
|
Sign up to set email alerts
|

Perancangan Tampilan Visual Docking Guidance System (Vdgs) Pada Sistem Parkir Pesawat Terbang

Abstract: Visual Docking Guidance System (VDGS), is a device provided by the airport service to assist a pilot parked the plane on the righr place. On Aircraft parking control activities in the airport, the pilot is assisted by a marshaller that aims to be steering the movement of aircraft to the correct parking spot. The more density of the movement of aircraft on the apron activity requires the use of alternative technology to substitute marshaller, this technology is called Visual Docking Guidance Syatem (VDGS). VDGS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…This guidance system is designed to provide fast, smooth, and precise docking guidance to the gate terminal. The Frequency Marker controls the aircraft type to ensure that it matches the information provided for docking [9]. It displays clear and visible information to the pilot on a high-intensity LED display for correct docking directions.…”
Section: Visual Guidance Displaymentioning
confidence: 99%
“…This guidance system is designed to provide fast, smooth, and precise docking guidance to the gate terminal. The Frequency Marker controls the aircraft type to ensure that it matches the information provided for docking [9]. It displays clear and visible information to the pilot on a high-intensity LED display for correct docking directions.…”
Section: Visual Guidance Displaymentioning
confidence: 99%
“…LiDAR sensors have been employed in different research to determine the direction of the aircraft's longitudinal motion in its parking system [14]. The research' findings suggested that the developed tool could provide information for the pilots in the form of a display that guides them to steer the aircraft to the right or left to align with the correct center line position.…”
Section: B Application Of Lidar Sensormentioning
confidence: 99%
“…Sejalan dengan perkembangan jaman dan kemajuan teknologi yang semakin tahun semakin pesat, hal ini menyebabkan pelayanan bandar udara melampaui kemampuan dalam menyediakan fasilitas untuk memenuhi pertumbuhan secara memadai [1]. Sebagian besar sistem transportasi udara di bandar udara ditekan melebihi kemampuan kapasitas rancangan bandar udara yang telah ada, sehingga mengakibatkan memburuknya pelayan di bandar udara [2].…”
Section: Pendahuluanunclassified